Neuroprotection by Transcranial Direct Current Stimulation in Rodent Models of Focal Ischemic Stroke: A Meta-Analysis - Huang, Jiapeng; Zhao, Kehong; Zhao, Ziqi; Qu, Yun (Frontiers in Neuroscience, 2021)
Infarct size is associated with stroke severity in clinical studies, so reducing it has become an important target and research hotspot in the treatment of ischemic stroke. Some preclinical studies have shown transcranial direct current stimulation (tDCS) reduced infarct size and improved neurological deficit, but others have not found beneficial effects. Besides, the optimal pattern of tDCS for ischemic stroke remains largely unknown. To shed light on the current circumstance and future research directions, the systematic review evaluated the effect of different tDCS paradigms in reducing infarct size and improving neurological deficit in rodent models of ischemic stroke and assessed the methodological quality of current literature. We searched the MEDLINE (via PubMed), EMBASE, Web of Science, and Scopus from their inception to August 18, 2021, to identify studies evaluating the effects of tDCS in rodent models of ischemic stroke. Eight studies were included, of which seven studies were included in the meta-analysis. The results showed cathodal tDCS, rather than anodal tDCS, reduced infarct size mainly measured by tetrazolium chloride and magnetic resonance imaging (standardized mean difference: -1.13; 95% CI: -1.72, -0.53; p = 0.0002) and improved neurological deficit assessed by mNSS (standardized mean difference: -2.10; 95% CI: -3.78, -0.42; p = 0.01) in an early stage of focal ischemic stroke in rodent models. Subgroup analyses showed effects of cathodal tDCS on infarct size were not varied by ischemia duration (ischemia for 1, 1.5, and 2 hours or permanent ischemia) and anesthesia (involving isoflurane and ketamine). The overall quality of studies included was low, thus the results must be interpreted cautiously. Published studies suggest that cathodal tDCS may be a promising avenue to explore for augmenting rehabilitation from focal ischemic stroke. Considering the methodological limitations, it is unreliable to blindly extrapolate the animal data to the clinical practice. Future research is needed to investigate the mechanism of tDCS in a randomized and blinded fashion in clinically relevant stroke models, such as elderly animals, female animals, and animals with comorbidities, to find an optimal treatment protocol.